Gender Integration for Inclusive Adaptation to Climate Risks - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Encouraging women farmer participation across all stages of the project via community-based groups, and capacity building efforts have created a platform for women to improve agency, confidence and decision making at the community level while pursuing income generating opportunities. With time, women are being entrusted with more roles and responsibilities in the agricultural sector, though the status of their authority and decision-making ability still offers immense scope for improvement. Women farmers are still not socially accepted as major contributors to the sector, while they struggle to fulfill the entrusted roles and responsibilities, in a patriarchal system. The project integrated gender concerns across all the stages of the project, starting from the planning stage itself.